Pengaruh Kualitas Infromasi, Kualitas Pelayanan, Dan Kualitas Sistem Terhadap Kepuasan Konsumen Berbelanja Pada Social Commere Tiktok Di Yogyakarta Dengan Model Delone dan McLean - Arif Sudaryana; Kharisma Zuliana; Anindita Imam Basri (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
Customer satisfaction is an important factor that determines the success of an application in retaining its users. This study aims to analyze the effect of information quality, service quality, and system quality on consumer satisfaction in shopping through the TikTok social commerce application in Yogyakarta. By involving 100 respondents selected using the purposive sampling method, data were collected through questionnaires and analyzed using multiple linear regression with the help of IBM SPSS 26. The results showed that information quality and system quality had a positive and significant impact on consumer satisfaction, while service quality did not have a significant effect. Overall, the three variables simultaneously influenced consumer satisfaction, with an F-count value of 91.560 and a significance of 0.000. The coefficient of determination (adjusted R²) of 74.1% indicated that these factors contributed to consumer satisfaction, while the remaining 25.9% was influenced by other variables not analyzed in this study.